2006
DOI: 10.1007/s11244-006-0017-6
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Catalytic Washcoat Geometry on Light-off in Monolith Reactors

Abstract: This paper presents the results of a series of simulations of the light-off of carbon monoxide in excess oxygen in a single channel monolith reactor. The catalytic washcoat geometry is tested for its effect on the light-off position and shape. The simulations used a combination of two and three-dimensional modelling with non-linear oxidation kinetics. Different temperature ramp rates were employed. It is seen that the shape of the washcoat has an influence on the shape of the light-off curve, especially for hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…To this effect, understanding the diffusion that occurs within the washcoat and substrate material which strongly affects reactor performance is essential in the design of monolith supported catalysts (Zhang et al 2004;Koci et al 2007; More et al 2006). With these factors in mind, it must be ac- knowledged that the diffusion coefficients reported in literature for microporous materials often vary with differences as large as five orders of magnitude being reported for different techniques (Kärger 2012).…”
mentioning
confidence: 99%
“…To this effect, understanding the diffusion that occurs within the washcoat and substrate material which strongly affects reactor performance is essential in the design of monolith supported catalysts (Zhang et al 2004;Koci et al 2007; More et al 2006). With these factors in mind, it must be ac- knowledged that the diffusion coefficients reported in literature for microporous materials often vary with differences as large as five orders of magnitude being reported for different techniques (Kärger 2012).…”
mentioning
confidence: 99%
“…We have shown that taking the real channel geometry into consideration can influence the predicted light-off curve significantly under some conditions. [73] As a final point, it is obviously essential to have good values for the effective diffusion coefficient. Typically, this must be done experimentally, but to make the measurements on real washcoats is quite tricky.…”
Section: Modelling the Washcoat Diffusionmentioning
confidence: 99%
“…In the beginning of the light-off region during heating the conversion with finite rate washcoat diffusion is larger than in the case with instantaneous washcoat diffusion. This increase in conversion due to finite rate washcoat diffusion is a known phenomena and is due to the negative reaction order of the overall reaction with respect to CO [26].…”
Section: Analysis Of the Reaction Mechanismmentioning
confidence: 99%